1999
DOI: 10.1016/s0926-860x(99)00031-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective N-monomethylation of aniline over Zn1−xNixFe2O4 (x=0, 0.2, 0.5, 0.8 and 1) type systems

Abstract: The reaction of aniline with methanol was carried out over Zn 1Àx Ni x Fe 2 O 4 (x0, 0.2, 0.5, 0.8 and 1) type systems in a ®xed-bed down-¯ow reactor. It was observed that systems possessing low``x'' values are highly selective and active for mono N-alkylation of aniline leading to N-methyl aniline. Selectivity for N-methyl aniline over ZnFe 2 O 4 was more than 99% under the optimized reaction conditions. Even at methanol to aniline molar ratio of 2, the yield of N-methyl aniline was nearly 55.5%, whereas its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…These results also indicated that this method for alkylation was feasible and convenient, although the yield of alkylates was lower (<52%) than that of chemical alkylation with a yield of 70-90% [2,3,[7][8][9][10][11]. Another limitation was that this process afforded a mixture of different alkylanilines products rather than pure alkylation product, which should be further improved for the industrial application.…”
Section: Large Proportion Catalysts > Small Proportion Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results also indicated that this method for alkylation was feasible and convenient, although the yield of alkylates was lower (<52%) than that of chemical alkylation with a yield of 70-90% [2,3,[7][8][9][10][11]. Another limitation was that this process afforded a mixture of different alkylanilines products rather than pure alkylation product, which should be further improved for the industrial application.…”
Section: Large Proportion Catalysts > Small Proportion Catalystsmentioning
confidence: 99%
“…Thus, alkylanilines formed the basic raw materials for synthesis of organic chemicals and chemical intermediates or additives in dyes, fuel oil, synthetic rubbers, explosives, herbicides, and pharmaceuticals [1][2][3][4][5]. The reaction involving the alkylation of aniline (PhNH 2 ) with base alcohol (MeOH, EtOH) had been previously studied using several different kinds of catalysts such as zeolites [6,7], composites [8][9][10][11][12][13][14][15], and clays [4]. However, all of the reactions catalyzed by these materials were carried out at higher temperature (200-400 • C), higher pressure, longer procedure, moreover, the catalysts used for the alkylation of aniline must be calcined.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal analysis using a TG-DTA instrument (SETARAM-TG-DTA-92) indicated that ferrite systems are thermally stable in the temperature range of 150-1000 • C without creating major weight losses, decompositions or phase transformations. Acidity values of the systems follow the following order: CF-5>ZCF-4>ZCF-3>ZCF-2>ZF-1; basicity values follow exactly the opposite trend (acidity and basicity were qualitatively measured using alcohol dehydration activity of the systems and adsorption experiments using organic molecules having different electron affinity values, respectively [11,12]). The BET surface areas of the different compositions of the systems were determined using an OMNISORP 100 CX instrument; the results are presented in Table 1.…”
Section: Catalyst Synthesis and Characterizationmentioning
confidence: 99%
“…Several reports have appeared on the alkylation of aniline using methanol as methylating agent. Our recent investigations on the alkylation of aniline using differ-ent ferrite systems revealed that Zn 1−x Co x Fe 2 O 4 and Zn 1−x Ni x Fe 2 O 4 (x=0, 0.2, 0.5, 0.8 and 1.0) systems possessing low 'x' values are exceptionally active and selective for N-monomethylation of aniline, when methanol is used as the alkylating agent [11,12]. In these communications, we have highlighted some distinct features of the systems, such as their high activity at comparatively low reaction temperatures and low methanol to aniline molar ratios, prolonged stability and NMA selectivity up to 98-99% under optimized reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Iron can be easily replaced in the magnetite structure by various other cations maintaining the spinel framework [3][4][5][6], and this can strongly affects the physico-chemical behavior of the resulting solid. Incorporation of transition metals such as Ni, Cu [7], Mn [4] or Co [3] in the spinel lattice can significantly modify the redox properties of ferrites and influences their stability.…”
Section: Introductionmentioning
confidence: 99%